Photo-induced nickel-mediated cross-electrophile coupling for alkylated allenes via electron donor–acceptor complexes. Issue 2 (15th November 2022) - Zhou, Zhao-Zhao; Zhai, Xiao-Feng; Zhang, Shu-Liang; Xia, Ke-Jian; Ding, Haixin; Song, Xian-Rong; Tian, Wan-Fa; Liang, Yong-Min; Xiao, Qiang
Abstract : The first photo-induced nickel-mediated regioselective radical–radical cross-electrophile coupling process with alkyl NHP esters and EDA complexes for alkylated allenes is described. Abstract : Herein, a highly regioselective alkylation of propargylic carbonates for trisubstituted allenes with alkyl N -hydroxyphthalimide (NHP) esters was developed via a nickel-mediated radical cross-electrophile coupling process. Electron donor–acceptor (EDA) complex photoactivation strategies have emerged as a versatile way for alkyl radicals. This method features mild conditions and a broad substrate scope and the involvement of primary alkyl radicals represents the first direct approach for primary alkylated allenes. Preliminary mechanistic studies indicated that this transformation proceeded through a radical–radical coupling process.